KEBIASAAN MAKAN MAKANAN TINGGI PURIN DENGAN KADAR ASAM URAT DI PUSKESMAS - Kussoy, Veronica Flaurensia Magdalena; Kundre, Rina; Wowiling, Ferdinand (Universitas Sam Ratulangi, 2019)
Abstract: Unhealthy community eating patterns by consuming high protein foods that contain high purine levels causes the incidence of hyperuricemia to increase. Consuming high purine foods will increase uric acid levels in the blood, which predisposes to gouty arthritis. The aim was to determine the Corelation between high purine food eating habits with uric acid levels in the working area of Remboken Community Health Center. The research design used descriptive analytic with Cross Sectional Study approach. A sample of 51 respondents was obtained using the Total Sampling technique. The results of statistical test studies using the Fisherâ€™s Exact Test at a significance level of 95%, obtained a significant value Ï = 0.034 <Î± (0.05). The conclusion is that there is a relationship between eating habits of high purine foods with uric acid levels.Keywords : Purines, Gout, Eating habitsAbstrak : Pola makan masyarakat yang tidak sehat dengan mengkonsumsi makanan berprotein tinggi yang mengandung kadar purin tinggi menyebabkan kejadian hiperurisemia semakin meningkat. Mengkonsumsi makanan tinggi purin akan meningkatkan kadar asam urat dalam darah, yang merupakan predisposisi terjadinya gout arthritis. Tujuan untuk mengetahui hubungan kebiasaan makan makanan tinggi purin dengan kadar asam urat di wilayah kerja puskesmas remboken. Desain penelitian yang digunakan yaitu Deskriptif Analitik dengan pendekatan Cross Sectional Study. Sampel berjumlah 51 responden yang didapat dengan menggunakan tehnik Total Sampling. Hasil penelitian uji statistik menggunakan uji Fisherâ€™s Exact Test pada tingkat kemaknaan 95%, didapatkan nilai signifikan Ï = 0,034 < Î± (0,05). Kesimpulan ada hubungan antara kebiasaan makan makanan tinggi purin dengan kadar asam urat.Kata kunci : Purin, Asam Urat, Kebiasaan makan